Identification of Risks Pertaining to Abandoned Housing Projects in Malaysia. (10th November 2015) - Abdul-Rahman, Hamzah; Wang, Chen; Ariffin, Nur Hamizah
Abstract : Housing industry is one of the most dynamic, risky, and challenging industries. In Malaysia, this industry has a poor reputation for managing risks, with many major projects failing to be completed within the allotted time. Due to the inherent risks involved in construction projects, it is essential to recognize the risks that cause problems associated with abandoned housing projects. Therefore, this study aims to identify the risks that contribute to issues of abandoned housing projects and to propose mitigation strategies. The methodologies used in this study are combination of qualitative and quantitative methods of literature review, questionnaire survey, and interview. The results show that many risks are involved in housing project, including risks related to environmental impacts, construction, politics, law, management, finance, materials, and economy, of which the probability of risks from unexpected ground condition, project delays, bureaucracy, contractual disputes between developer and landlord, weakness in management by inexperience developer, and financial crisis is very high. It was also found that all relevant parties involved in housing industry are required to have extensive cooperation in advance and should perform systematic risk management strategies in order to mitigate the risks leading to problems associated with abandoned housing projects.